Pengaruh Persepsi Mahasiswa Tentang Kompetensi Profesional Dosen terhadap Prestasi Belajar yang Dimediasi oleh Motivasi Belajar Mahasiswa - Misde none Yola; Tugiyo Tugiyo (Universitas Negeri Malang, 2022)
Abstract: The purpose of this study was to determine the positive effect of student perceptions about the professional competence of lecturers in research methodology subjects on student achievement. The research method used is descriptive associative research, the analysis used is Path Analysis. Research variables include: the professional competence of lecturers in the research methodology subject (X1), learning motivation (X2), and learning achievement (Y). The population in this study were lecturers at the Ministry of Health Jakarta 2 Poltekes who were certified educators, the sample of this study was a lecturer at the Ministry of Health Jakarta 2 Poltekes who were certified educators who taught research methodology courses. The number of research samples was 10 lecturers who taught research methodology courses, which were distributed in 6 departments at the Poltekkes Kemenkes Jakarta II. Research respondents were students who were taking research methodology courses, totaling 315 students who were divided into 7 classes. Taking respondents in this study using the technique